ANALISIS HUBUNGAN ANTARA LAMA STUDI, JALUR MASUK DAN INDEKS PRESTASI KUMULATIF (IPK) MENGGUNAKAN MODEL LOG LINIER (STUDI KASUS: LULUSAN MAHASISWA FSM UNDIP PERIODE WISUDA TAHUN 2012/2013) - Diah Budiati; Yuciana Wilandari; Suparti Suparti (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2014)
Graduation is the end result of the process learning during the lectures in college. One of the duties and responsibilities of the college is to produce quality graduates, which college will prepare candidates reliable scholars, achievers and have special expertise in the field. To achieve S1 degree course each student must complete his college studies load. In the process of completion of the study load many factors at play, both internal and external factors. These factors are not directly specify a person in graduation. In this study, the internal factors are long study, driveways and university grade point average (GPA) of students. The purpose of this study was to determine the relationship between the internal factors in terms of graduation. One method used to determine the relationship between the factors is log linear models. Estimating a log linear model using the Maximum Likelihood Estimation (MLE), which is followed by Newton-Raphson iteration. Selection of the best model was conducted using Backward Elimination. To test the significance of the model has been obtained to use Goodness of Fit Test. After testing on the whole, it is known that each of the factors that play a role in graduate student tested and there was an interaction between the period of study with a GPA of factors.